The Scope of Taqlid - Taha J. al 'Alwani (American Journal of Islam and Society, 1992)
It is generally agreed that taqlid is not allowed in the case of fundamental beliefs, such as the existence of God and His attributes. The teason for this is that such questions ate to be answered by the individual on the basis of his/her own knowledge and conviction, while taqlid repments reliance on the knowledge of others. Another teason for this is that there is only one truth in such matters, and all who call themselves Muslims must recognize, know, and be lieve in these articles of faith. Anything else would be heresy and disbelief. The scope of taqlid is thus limited to the interpretation of particular aspects of Shari'ah rulings. Rulings on essential knowledge (ma'lum bi al darurah) about Islam' (i.e., testifying aloud; believing in the heart that God is One and has no partner. that there is no being like or similar to Him; that He neither gives birth nor was given birth to; that He has no equal; that He is the Creator of all and the One to which all creation will durn; that He, the Eternal, gives and takes away life; that He and His attributes and person have no beginning and no end; and that He is the possessor of (sits upon) all (the throne of) power, m thus beyond the Teach of taqlid. Each Muslim is required to acquire a knowledge of these and other similar matters. It was for this reason that the Prophet said "Seeking knowledge is the duty of every Muslim"' Nonetheless, certain scholars ate of the opinion that taqlid is allowed even in such fundamental mattes. This opinion, however, is without substance, for taqlid, as discussed above, is essentially an allowance granted to those without access to the relevant texts of the Qur'an or Sunnah. These mattes cannot be categorized as such, for they are both available and totally clear to each Muslim, meaning that they are not in need of any interpretation through ijtihad ...